RP-HPLC Method for Simultaneous Estimation of Rutin and Berberine in Bulk and Anti-Urolithiatic Formulation - Kasetti, Kalyani; Bandhakavi, Sailaja (Asian Journal of Chemistry, 2023)
Standardization of active phytochemicals is essential for the quality assessment of herbal formulations. In current study a new, simple, rapid and economical RP-HPLC technique was developed and validated for simultaneous estimation of marker compounds rutin and berberine. The mobile phase used was a mixture of acetonitrile, 0.1% orthophosphoric acid in the ratio of 50:50 v/v on a Shiseido Capcell pak C18 column (250 × 4.6 mm, 5 μ) with wavelength detection using UV detector at 265 nm. The time taken for elution of rutin and berberine were 2.27 and 3.31 min, respectively. The linearity range for both rutin and berberine was observed from 5 to 25 μg/mL with correlation co-efficient of 0.997 and 0.999, respectively. The developed method was precise with % relative standard deviation value < 2 for both intra- and inter-day precision. The accuracy of the developed method was accomplished at three concentration levels and the recovered percentage was 99-100.2%. The developed and validated technique was successfully used as standardization tool for the simultaneous determination of markers rutin and berberine in the marketed anti-urolithiatic homeopathic formulation.